The Impact of Worker Satisfaction and Work Equipment on Service Performance Handling of Ship Waste at Port Tanjung Priok Port - Radelas Nur Wahzzaituni; Ade Rizki Andreas; Yosi Pahala (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to determine the relationship between worker satisfaction and work equipment to service performance in the context of handling ship waste at Tanjung Priok Port. By examining the impact of these factors, this study aims to identify strategies to improve operational efficiency and overall service quality. Data was collected through surveys and interviews with workers and waste treatment management at the port. These findings show a strong impact when worker satisfaction and equipment are tested against service performance, with satisfied employees and adequate equipment showing higher levels of commitment and productivity. As well as the importance of well-maintained and appropriate work equipment in supporting efficient operations and reducing downtime. Based on these results, recommendations were given to increase worker satisfaction and optimize work equipment to improve the performance of ship waste handling services at Tanjung Priok Port as a whole.